"We are doing it together"; The integral role of caregivers in a patients' transition home from the medicine unit. - Shoshana Hahn-Goldberg; Lianne Jeffs; Amy Troup; Rasha Kubba; Karen Okrainec (PLoS ONE)
Background An admission to hospital for acute illness can be difficult for patients and lead to high levels of anxiety. Patients are given a lot of information throughout their hospital stay and instructions at discharge to follow when they get home. For complex medical patients, the ability to retain, understand, and adhere to these instructions is a critical marker of a successful transition. This study was undertaken to explore factors impacting the ability of patients to understand and adhere to instructions. Methods A qualitative design of interviews with patients and caregivers was used. Participants were adult patients and caregivers with congestive heart failure, chronic obstructive pulmonary disease, or community-acquired pneumonia being discharged home from three academic acute care hospitals in Ontario, Canada. Semi structured interviews were conducted with participants within one week following their discharge from hospital. Interviews were audiotaped and transcribed. Five independent researchers participated in an iterative process of coding, reviewing, and analyzing the interviews using direct content analysis. Results In total, 27 participants completed qualitative interviews. Analysis revealed the role of the caregiver to be critical in its relation to the ability of patients to understand and adhere to discharge instructions. Within the topic of caregiving, we draw on three areas of insight: The first clarified how caregivers support patients after they are discharged home from the hospital. The second highlighted how caregiver involvement impacts patient understanding and adherence to discharge instructions. The third revealed system factors that influence a caregiver's involvement when receiving discharge instructions. Conclusion Caregivers play an important role in the transition of a complex medical patient by impacting a patient's ability to understand and adhere to their discharge instructions. The themes identified in this paper highlight opportunities for healthcare providers and institutions to effectively involve caregivers during transitions from acute care hospitals to home.